Effects of almix 20wp on selected sedges and broadleaf weeds in rice (Bangladesh Journal of Botany, 2025)
An investigation was conducted to assess the efficacy and crop tolerance of Almix 20WP, a herbicide premix of metsulfuron-methyl and chlorimuron-ethyl, for controlling sedges and broadleaf weeds in flooded rice fields. Treatments included various rates of Almix 20WP, 2,4-D, Bentazone-sodium, Bispyribac-sodium, and a tank-mix of Almix 20WP (40 g/ha) with 2,4-D (1000 g/ha). Almix 20WP at 60 g/ha significantly reduced weed biomass and density. Bentazone-sodium treated rice yielded the highest grain (7975.0 kg/ha), with the tank-mix of Almix 20WP and 2,4-D provided the second-highest (7962.5 kg/ha). Almix 20WP showed excellent control of weeds like Cyperus difformis, Fimbristylis miliacea, and Ludwigia octovalvis, with the tank-mix enhancing control of Cyperus iria. Thus, Almix 20WP at 40 g/ha is recommended for flooded fields to control sedges and broad leaf weeds.Bangladesh J. Bot. 54(2): 185-190, 2025 (June)